1984
DOI: 10.1099/00207713-34-1-45
|View full text |Cite
|
Sign up to set email alerts
|

Attempts to Classify Herbicola Group-Enterobacter agglomerans Strains by Deoxyribonucleic Acid Hybridization and Phenotypic Tests

Abstract: There are seven names on the Approved Lists of Bacterial Names that have been treated as partial or total synonyms for strains belonging to the Enterohucter agglomerans-Herbicola group of Erwiniu species complex. A total of 124 strains belonging to this complex, isolated mainly from plant and human sources, were studied by deoxyribonucleic acid relatedness and by a variety of biochemical tests. Ninety of these strains fell into 13 deoxyribonucleic acid hybridization groups (2 to 13 strains per group), and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 22 publications
2
47
0
Order By: Relevance
“…o op pe en nU UP P ( (J Twenty-four Pantoea strains used in this study were previously used in DNA hybridisation studies [4], [5], [9], [10], [11] and [12] and are regarded as reference strains (Fig. 1).…”
Section: Faflp Analysis Of Pantoea Speciesmentioning
confidence: 99%
“…o op pe en nU UP P ( (J Twenty-four Pantoea strains used in this study were previously used in DNA hybridisation studies [4], [5], [9], [10], [11] and [12] and are regarded as reference strains (Fig. 1).…”
Section: Faflp Analysis Of Pantoea Speciesmentioning
confidence: 99%
“…Clustering between strains within a group was not identical in the two methods, but these fluctuations at the subgroup level are inconsequential as long as the aim is to ensure that strains remain within a species. Misidentified strains previously grouped into P. agglomerans were accurately assigned to P. ananatis, P. dispersa, or the recently defined species P. vagans or to discrete clades following Brenner's biogroups (10). For example, strains could be assigned to biogroup VII (LMG 5336, ATCC 27993, ATCC 27994, and EM2cb), biogroup VIII (LMG 5341, ATCC 27991, and ATCC 27992), and biogroup XII (LMG 5337, ATCC 27981, and ATCC 27990) using both MALDI-TOF MS and gyrB sequencing (Fig.…”
mentioning
confidence: 99%
“…Interest in the "herbicola" group peaked in 1971, when such organisms were implicated in a nosocomial septicemia outbreak in the United States resulting from contaminated intravenous products in which 40 of 378 patients died (4,40). Ewing and Fife (19,20) compared the isolates from these patients with representatives of the "herbicola" group and concluded that the two sets of strains belonged to the same species.…”
mentioning
confidence: 99%